Knowledgeability about organic food consumption and the factors behind it - Barua, Sukanya; Satyapriya,; Kumar, Rajeev; Sangeetha, V.; Muralikrishan, L.; Wason, Monika (Frontiers in Nutrition, 2023)
Introduction The popularity of organic food is in increasing trend due to the increased existence of synthetic food worldwide. Hence it is very important to know the knowledge level of city dwellers regarding various aspects of organic food and factors associated with their awareness level. Objectives The primary objective of this research study is to develop a standardized knowledge test to assess the knowledge level of respondents regarding organic food and find out the factors behind elevated knowledge levels. Methods A standardized knowledge test was developed comprising 26 knowledge items and pilot tested on 42 individuals. Difficulty index, discrimination index and point biserial correlation coefficient were calculated; only 21 knowledge statements were selected out of 26. The reliability coefficient and validity were checked and found satisfactory. The final knowledge test containing 21 knowledge statements was administered to 1050 respondents from various locations of the National Capital Region (NCR)-Delhi, India. After getting the knowledge score from each individual, it was classified as very low, low, medium, high and very high knowledge level. For determining factors contributing towards enhanced knowledge level, the correlation coefficient was calculated between independent socio-economic variables of each individual and their corresponding knowledge score. Regression analysis was also performed and developed a model to depict a relationship between the dependent variable i.e. knowledge level and independent variables. Results Standardized knowledge test depicted that a major portion of respondents (62.0%) possessed very low, low and medium levels of knowledge, whereas 23.5 and 14.5% of respondents had high and very high levels of knowledge regarding organic food. Independent variables like gender, education, family size, family income, internet, mass media exposure and social participation had a positive relationship with the knowledge level of respondents. The results of regression analysis show that education (X2), total annual income (X3), gender (X6), participation in various organizations like the club, societies, etc. (X8), health consciousness of individual (X11), perception of organic food (X13); could explain the major share of ~62.1% of the variation in dependent variable i.e. knowledge level. Conclusion The developed standardized knowledge test for the present study was found valid and appropriate research tool for evaluating the knowledge level of urban citizens regarding organic food. The majority of respondents had a positive attitude towards organic food but possessed low to medium knowledge levels regarding organic food. Occasional awareness campaigns and capacity-building programs regarding various aspects of organic food in educational institutes, residential societies and through mass media can be beneficial to society.